Antivirulence Strategies for the Treatment of Staphylococcus aureus Infections: A Mini Review - Ford, Caleb A.; Hurford, Ian M.; Cassat, James E. (Frontiers in Microbiology, 2021)
Staphylococcus aureus is a Gram-positive bacterium capable of infecting nearly all host tissues, causing severe morbidity and mortality. Widespread antimicrobial resistance has emerged among S. aureus clinical isolates, which are now the most frequent causes of nosocomial infection among drug-resistant pathogens. S. aureus produces an array of virulence factors that enhance in vivo fitness by liberating nutrients from the host or evading host immune responses. Staphylococcal virulence factors have been identified as viable therapeutic targets for treatment, as they contribute to disease pathogenesis, tissue injury, and treatment failure. Antivirulence strategies, or treatments targeting virulence without direct toxicity to the inciting pathogen, show promise as an adjunctive therapy to traditional antimicrobials. This Mini Review examines recent research on S. aureus antivirulence strategies, with an emphasis on translational studies. While many different virulence factors have been investigated as therapeutic targets, this review focuses on strategies targeting three virulence categories: pore-forming toxins, immune evasion mechanisms, and the S. aureus quorum sensing system. These major areas of S. aureus antivirulence research demonstrate broad principles that may apply to other human pathogens. Finally, challenges of antivirulence research are outlined including the potential for resistance, the need to investigate multiple infection models, and the importance of studying antivirulence in conjunction with traditional antimicrobial treatments.